DETERMINANT OF FINANCIAL DISTRESS: THE CASE OF PULP & PAPER COMPANIES REGISTERED IN INDONESIA STOCK EXCHANGE - Augustina Kurniasih; Heliantono; Agus Herta Sumarto; Rianti Setyawasih; Isti Pujihastuti (School of Business, Bogor Agricultural University (SB-IPB), 2020)
The pulp and paper industry contributes to the Indonesian economy, especially to the non-oil and gas processing industry. Empirical research shows that pulp and paper companies listed on the Indonesia Stock Exchange (IDX) indicated financial distress. This study aims to find the effect of liquidity, leverage, profitability, and efficiency on pulp & paper companies' financial distress listed on the IDX. Using the Altman Z-score as a measure of financial distress, it was found that profitability, efficiency, and liquidity had a significant adverse effect on financial distress. In contrast, leverage had a significant positive effect on financial distress. Profitability has the greatest influence on financial distress, so it needs the primary intention of management. Keywords: financial distress, liquidity, profitability, leverage, efficiency